Transformation, transition or stagnation: understanding change in a globalizing economy - Prasad, G. S. Ganesh (ed.) (Chennai, 2007)
The papers in this volume, presented at the Sixth Development Convention organized by the Madras Institute of Development Studies in February 2007, consolidate our understanding of the issues and experiences in the field of 'development. They deliberate upon development with a scholarly emphasis on the 'change that the process has brought about. The focus is to examine not just the social impact but the social content of macro-economic and social plans and programmes. These papers attempt to capture the change and analyze the linkages between macro-economic concerns and the ground level impacts: sectoral changes and the impact of these changes on the i citizen-state relationships
Proceedings of the 6th development convention 2007
Keywords: Economic policy-India